A metal lithium battery and a preparation method thereof

CN122762779APending Publication Date: 2026-09-15CHINA ENERGY LITHIUM
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202510292825.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-03-12
Publication Date
2026-09-15

AI Technical Summary

Technical Problem

[0004]然而,金属锂在循环过程中仍存在金属锂粉化、安全性低问题,且金属锂的熔点为180℃,该锂电池无法通过动力电池200℃热箱试验

Benefits of technology

[0048] 1. The lithium metal battery provided by the present invention uses a particulate dual-framework lithium-carbon composite material as the negative electrode material, selects lithium boron particles with a specific active lithium content as the core, and sets a three-dimensional porous carbon framework space layer on it, thus constructing a three-dimensional distributed dual-framework structure in the negative electrode phase. It is more stable than a single lithium boron alloy framework or a three-dimensional porous carbon framework space layer, which can effectively solve the problems of volume expansion of lithium metal and pulverization during cycling, and improve the cycle performance and safety of the lithium metal battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122762779A_ABST
    Figure CN122762779A_ABST
Patent Text Reader

Abstract

The application discloses a metal lithium battery and a preparation method thereof. The metal lithium battery comprises a positive electrode, a diaphragm and a negative electrode, the negative electrode comprises a metal lithium composite material layer, the metal lithium composite material layer comprises a granular double-skeleton lithium-carbon composite material, the double-skeleton lithium-carbon composite material takes a lithium-boron particle as a core, the core has a lithium-boron alloy structure skeleton and active lithium, and a three-dimensional porous carbon skeleton space layer formed by nano carbon material is arranged on the surface of the core. The carbon skeleton space layer formed by the nano carbon material in the double-skeleton lithium-carbon composite material can simultaneously conduct lithium ions and electrons, is beneficial to the uniform distribution of the lithium ions and the electrons, and inhibits the generation and growth of lithium dendrites; the lithium-boron alloy porous structure and the carbon skeleton space layer formed by the carbon material constitute double skeletons. The metal lithium battery has small volume change, long cycle life and high temperature resistance of above 200 DEG C, and is one of candidates of power batteries.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of battery technology, and in particular to a lithium metal battery and its preparation method. Background Technology

[0002] Lithium metal possesses extremely high theoretical specific capacity and extremely low electrochemical potential, making lithium metal batteries one of the most widely used and promising batteries in the world today, and a likely candidate for high-energy-density batteries. However, various problems still need to be solved in the practical application of the negative electrode in lithium metal batteries. Among these, the most important are the issues of volume expansion and lithium dendrite formation in the lithium negative electrode during charge and discharge.

[0003] Currently, common methods for suppressing lithium dendrites include: setting protective layers on lithium alloys and metallic lithium surfaces, and developing lithium-carbon composite materials. These methods have each addressed the dendrite growth problem of lithium metal anodes during charge-discharge cycles to some extent, but each also has its own limitations. CN117446798A discloses a lithium battery in which the anode is obtained by uniformly depositing metallic lithium into graphitized carbon material. The deposition of metallic lithium in graphitized carbon material results in lithium intercalation, forming LiC6. The generated LiC6 is an excellent lithiophilic site, inducing uniform and dense deposition of metallic lithium, regulating the distribution of lithium ions on the electrode surface, avoiding the aggregation of lithium ions in time and space, and achieving uniform deposition of lithium ions on the anode surface, thereby suppressing dendrite growth.

[0004] However, lithium metal still suffers from problems such as lithium metal pulverization and low safety during cycling, and lithium metal has a melting point of 180°C, so this lithium battery cannot pass the 200°C hot box test for power batteries.

[0005] Therefore, how to design a lithium metal battery that can simultaneously solve the problems of lithium dendrite formation and lithium metal pulverization during cycling, and can combine rate performance, cycle performance and safety performance, and pass the 200℃ hot box test, has become an urgent problem to be solved. Summary of the Invention

[0006] To address the shortcomings of existing technologies, this invention provides a lithium metal battery, its preparation method, and the lithium metal battery itself. The negative electrode material of the lithium metal battery utilizes a granular dual-framework lithium-carbon composite material, constructing a three-dimensionally distributed dual framework within the negative electrode. This structure exhibits good stability and allows for simultaneous regulation of lithium-ion and electron transport, enabling the lithium metal battery to achieve excellent rate performance while maintaining high safety.

[0007] The objective of this invention is achieved through the following technical solution:

[0008] In a first aspect, the present invention provides a lithium metal battery, the lithium metal battery comprising a positive electrode, a separator and a negative electrode, the negative electrode comprising a lithium metal composite material layer, the lithium metal composite material layer comprising a particulate dual-framework lithium-carbon composite material; the particulate dual-framework lithium-carbon composite material having lithium boron particles as a core, the core having a lithium boron alloy structural framework and active lithium, and a three-dimensional porous carbon framework space layer formed by nano-carbon materials disposed on the surface of the core, wherein the active lithium in the lithium boron particles accounts for 50%-90% by mass.

[0009] In this invention, nano-carbon material refers to carbon material that is nano-sized in one dimension.

[0010] In this invention, the lithium-boron particles are composed of a three-dimensional porous lithium-boron alloy Li7B6 structural framework and active lithium (or free lithium) filled in the structural framework. The lithium-boron alloy Li7B6 can serve as an internal structural framework, which has good mechanical and thermal stability. It can not only adjust the amount of free lithium by controlling the raw material feeding ratio to achieve adjustable specific capacity, but also store lithium, thereby alleviating the volume expansion problem of metallic lithium while improving thermal stability.

[0011] The lithium metal battery provided by this invention comprises a lithium metal composite material layer made of granular dual-framework lithium-carbon composite material. The dual-framework lithium-carbon composite material has a lithium-boron alloy structural framework and a three-dimensional porous carbon spatial framework, forming a dual-framework structure design. The framework in the lithium metal composite material layer is continuous and has good structural stability, which can buffer the bulk expansion problem of lithium metal. It exhibits better negative electrode performance than single nano-carbon materials or lithium-boron alloy particles as the framework, with lower lithium metal pulverization during cycling, greatly improving battery safety. The granular dual-framework lithium-carbon composite material exists in a close-packed form within the lithium metal composite material layer. The three-dimensional porous carbon framework constructs a three-dimensionally distributed lithium-ion transport channel and electronic conductivity network in the composite negative electrode, allowing for simultaneous regulation of lithium-ion and electron transport, solving the problem of poor conductivity of lithium-boron alloys while suppressing lithium dendrite formation. The lithium-boron alloy structural framework possesses excellent mechanical and thermal stability. Not only can the amount of active lithium be controlled by adjusting the raw material feeding ratio to achieve adjustable specific capacity, but it can also store lithium (providing space for lithium from the positive electrode), thus alleviating the volume expansion problem of metallic lithium while improving thermal stability. Furthermore, it provides support for the three-dimensional porous carbon framework, giving the composite anode excellent conductivity, structural stability, and safety, as well as superior rate performance and cycle performance.

[0012] Optionally, the thickness of the negative electrode is 1-100μm, for example, it can be 1μm, 3μm, 5μm, 10μm, 20μm, 30μm, 40μm, 50μm, 70μm, 90μm or 100μm, etc., including but not limited to the listed values, preferably 5-50μm.

[0013] Optionally, the volume expansion rate of the lithium metal battery after cycling is ≤15%. The "after cycling" figure is based on the data that the discharge capacity decays to 80% of the initial discharge capacity or the charge / discharge efficiency is less than 98% during 0.5C / 1C testing.

[0014] Optionally, the melting point of the dual-framework lithium-carbon composite material is >200℃, and the composite anode has good high-temperature resistance and is expected to pass the 200℃ hot box test, making it one of the candidate anodes for power batteries.

[0015] Optionally, the average particle size of the dual-framework lithium-carbon composite material is 1-200 μm, for example, it can be 1 μm, 3 μm, 5 μm, 10 μm, 15 μm, 20 μm, 50 μm, 80 μm, 90 μm, 100 μm, 120 μm, 150 μm, 180 μm, 190 μm, 195 μm or 200 μm, etc., including but not limited to the listed point values, preferably 5-100 μm, and more preferably 10-50 μm.

[0016] Optionally, the lithium boron particles may have at least one of the following shapes: spherical, ellipsoidal, near-spherical, rod-shaped, or irregular.

[0017] Optionally, the active lithium content in the lithium-boron particles is 50%-90% by mass, preferably 50%-80%. Taking the mass of the lithium-boron particles as 100%, the active lithium content can be 50%, 52%, 55%, 58%, 60%, 65%, 70%, 75%, 80%, 85%, or 90%, etc. However, it is not limited to the listed values; as long as it is within the defined range, it falls within the protection scope of this invention. A higher active lithium content results in a smaller structural framework, which is detrimental to the structural stability of the composite anode. A lower active lithium content results in greater hardness of the dual-framework lithium-carbon composite material, poorer processing performance, and more defects in the resulting composite anode, or makes it more difficult to fabricate a composite anode.

[0018] Optionally, the structure of the three-dimensional porous carbon framework spatial layer is a three-dimensional porous network structure formed by interweaving at least one of linear, tubular or sheet-like nano-carbon materials.

[0019] Optionally, the nanomaterial includes at least one of carbon nanofibers, single-walled carbon nanotubes, few-walled carbon nanotubes, multi-walled carbon nanotubes, or graphene. Preferably, a combination of two different nanomaterials is used, such as carbon nanofibers and graphene, single-walled carbon nanotubes and multi-walled carbon nanotubes, few-walled carbon nanotubes and graphene, etc., including but not limited to the combinations listed above.

[0020] It should be noted that single-walled carbon nanotubes have a diameter of less than 2 nm, multi-walled carbon nanotubes have a diameter between 10 and 100 nm, and carbon nanotubes with a diameter between single-walled and multi-walled carbon nanotubes are called few-walled carbon nanotubes.

[0021] Optionally, the length of the linear and / or tubular carbon material is independently 1-100 μm, for example, it can be 1 μm, 1.5 μm, 3 μm, 4 μm, 4.5 μm, 5 μm, 7 μm, 10 μm, 20 μm, 40 μm, 45 μm, 50 μm, 70 μm, 90 μm or 100 μm, etc. The linear and / or tubular materials within the length range can easily interweave to form a three-dimensional network structure, including but not limited to the listed point values, preferably 5-50 μm.

[0022] Optionally, the diameter of the linear and / or tubular carbon material is independently 2nm-200nm, for example, it can be 2nm, 2.5nm, 3nm, 5nm, 10nm, 20nm, 50nm, 70nm, 90nm, 95nm, 100nm, 120nm, 150nm, 170nm, 190nm or 200nm, etc., including but not limited to the listed point values. The three-dimensional network structure that is easily interwoven by the linear and / or tubular materials within the diameter range is preferably 2nm-100nm.

[0023] Optionally, the planar size of the sheet material is 1-100 μm, for example, it can be 1μm, 1.5μm, 3μm, 4μm, 4.5μm, 5μm, 7μm, 10μm, 20μm, 40μm, 45μm, 50μm, 70μm, 90μm or 100μm, etc., including but not limited to the listed point values. The three-dimensional network structure that the sheet material can easily interweave within the planar size range is preferably 5-50μm.

[0024] Optionally, the thickness of the sheet material is 1-20 nm, for example, it can be 1 nm, 1.5 nm, 2 nm, 2.5 nm, 3 nm, 5 nm, 8 nm, 10 nm, 12 nm, 15 nm, 18 nm or 20 nm, etc., including but not limited to the listed point values. The sheet material within the thickness range can easily interweave to form a three-dimensional network structure, preferably 2-15 nm.

[0025] Optionally, the composite material further includes granular nano-carbon material, preferably at least one of biochar, conductive graphite, acetylene black, Ketjen black, Super P or Cabot carbon black, wherein the granular carbon material is distributed at any position on the surface of lithium boron particles, on the surface of the three-dimensional porous carbon skeleton space layer or in the pores.

[0026] Optionally, the mass ratio of the three-dimensional porous carbon framework space layer to the lithium boron particles is 1:(1-200), for example, it can be 1:1, 1:3, 1:5, 1:10, 1:15, 1:20, 1:30, 1:50, 1:100, 1:20, 1:40, 1:50, 1:180, 1:190, 1:195 or 1:200, etc., including but not limited to the listed values. The mass ratio can effectively alleviate the volume expansion of lithium boron particles during charging and discharging, while also taking into account the specific capacity. Preferably, it is 1:(5-150).

[0027] Optionally, the thickness of the three-dimensional porous carbon framework spatial layer is 2nm-5μm, for example, it can be 2nm, 5nm, 10nm, 20nm, 50nm, 100nm, 300nm, 500nm, 700nm, 1μm, 3μm, 4μm, 4.5μm or 5μm, etc., including but not limited to the listed values. If the thickness is too small, it is not easy to form a three-dimensional porous framework layer. If the thickness is too large, there will be more inactive substances, which is not conducive to improving the energy density of the material. Preferably, it is 10nm-3μm.

[0028] Optionally, the mass ratio of the three-dimensional porous carbon framework space layer to the boron in the lithium boron particles is 1:(0.1-100), for example, it can be 1:0.1, 1:0.3, 1:0.5, 1:1, 1:1.5, 1:2, 1:3, 1:4, 1:4.5, 1:5, 1:10, 1:30, 1:40, 1:50, 1:80, 1:95 or 1:100, etc., including but not limited to the listed values. The mass ratio is beneficial to constructing a negative electrode that is resistant to high temperature, has a stable structure and excellent cycle performance, and is beneficial to improving the safety performance and cycle performance of lithium metal batteries. Preferably, it is 1:(1-50).

[0029] Optionally, the diaphragm includes polypropylene, polyethylene, polypropylene / polyethylene composite diaphragm or polypropylene, polyethylene, or polypropylene / polyethylene composite diaphragm with coating;

[0030] Optionally, the coating includes at least one of boehmite, alumina, MOFs (metal-organic frameworks), COFs (covalent organic frameworks), solid electrolyte, sulfonated membrane, polyvinylidene fluoride (PVDF), aramid, or polyimide; the coating is lithium-friendly, can induce uniform lithium deposition, inhibit lithium dendrite growth, and further improve the safety of lithium.

[0031] Preferably, the negative electrode further includes a current collector, which includes at least one of pure copper foil, carbon-coated copper foil, roughened copper foil, nickel foil, copper-nickel alloy foil, copper-tin composite foil, stainless steel foil, carbon cloth, or carbon paper.

[0032] Preferably, the positive electrode comprises at least one of lithium iron phosphate, lithium manganese iron phosphate, lithium nickel cobalt manganese oxide, lithium nickel cobalt aluminum oxide, lithium manganese oxide, lithium cobalt oxide, lithium nickel oxide, elemental sulfur, lithium-rich manganese-based oxide, polyacrylonitrile sulfide, or vanadium pentoxide, and more preferably at least one of lithium nickel cobalt manganese oxide, lithium nickel cobalt aluminum oxide, or lithium-rich manganese-based oxide. This preferred positive electrode is advantageous for obtaining batteries with high energy densities of 450 Wh / kg or higher.

[0033] In a second aspect, the present invention provides a method for preparing a lithium metal battery as described in the first aspect above, the method comprising:

[0034] (1) Under an inert gas protective atmosphere, an organic solvent, lithium boron particles and carbon materials are mixed, wherein the carbon materials include nano-carbon materials and optionally, particulate nano-carbon materials, and then dispersed at high speed and / or spray-dried at a speed of more than 6000 rpm, thereby setting a three-dimensional porous framework space layer formed by the nano-carbon materials on the surface of the lithium boron particles to obtain a dual-framework lithium-carbon composite material; wherein the organic solvent is inert to the lithium boron particles;

[0035] (2) The composite negative electrode is prepared by using a dry process to prepare the dual-framework lithium-carbon composite material in step (1);

[0036] (3) Assemble the positive electrode, separator and negative electrode into the metal lithium battery.

[0037] Optionally, the organic solvent in step (1) includes any one or a combination of at least two of the following: liquid alkanes with 4-20 carbon atoms, liquid cycloalkanes with 4-20 carbon atoms, toluene, xylene, solvent oil, liquid paraffin, tetrahydrofuran, N-methylpyrrolidone, N,N-dimethylformamide, or silicone oil.

[0038] Optionally, the mass ratio of the organic solvent to the lithium boron particles in step (1) is (10-100):1, preferably (20-50):1.

[0039] Optionally, the high-speed dispersion in step (1) can be performed at a speed of 6000-15000 rpm for 10-100 min. For example, the speed can be 6000 rpm, 6500 rpm, 7000 rpm, 75000 rpm, 8000 rpm, 8500 rpm, 9000 rpm, 10000 rpm, 11000 rpm, 11500 rpm, 12000 rpm, 12500 rpm, 13000 rpm, 14000 rpm, 14500 rpm, or 15000 rpm, and the time can be 10 min, 20 min, 30 min, 50 min, 60 min, 70 min, 80 min, 90 min, or 100 min, etc. Preferably, the speed is 8000-12000 rpm and the time is 30-60 min.

[0040] Optionally, the inlet air temperature for spray drying is 180~240℃, for example, it can be 180℃, 185℃, 190℃, 200℃, 210℃, 220℃, 230℃ or 240℃, etc., including but not limited to the values ​​listed above, preferably 200~220℃.

[0041] Optionally, the outlet air temperature of the spray dryer is 80~120℃, for example, it can be 80℃, 85℃, 90℃, 100℃, 110℃ or 120℃, etc., including but not limited to the values ​​listed above, preferably 100~110℃.

[0042] Optionally, the atomization pressure of the spray drying is 0.1~0.5 MPa, for example, it can be 0.1 MPa, 0.15 MPa, 0.2 MPa, 0.25 MPa, 0.3 MPa, 0.35 MPa, 0.4 MPa, 0.45 MPa or 0.5 MPa, etc., including but not limited to the values ​​listed above, and preferably 0.2~0.4 MPa.

[0043] Optionally, the dry process in step (2) includes at least one of roll pressing and / or flat pressing, electrostatic spraying, or adhesive fiberization.

[0044] For example, the roll forming and / or flat forming process can form a material containing a dual-framework lithium-carbon composite material by passing it through the roll gap of a roll forming equipment or a flat forming mold, supported by materials such as release film; the electrostatic spraying process is to mix a binder and a dual-framework lithium-carbon composite material, and then spray it onto the surface of the current collector or support material through a spray gun; the binder fiberization process is to mix a binder and a dual-framework lithium-carbon composite material, then perform binder fiberization treatment, and finally perform hot roll forming.

[0045] Optionally, the adhesive includes at least one of polytetrafluoroethylene, polyvinylidene fluoride, or styrene-butadiene rubber.

[0046] Optionally, the mass ratio of the binder to the dual-framework lithium-carbon composite material is (1-20):(80-99), preferably (3-10):(90-97).

[0047] Compared with the prior art, the beneficial effects of the present invention are as follows:

[0048] 1. The lithium metal battery provided by the present invention uses a particulate dual-framework lithium-carbon composite material as the negative electrode material, selects lithium boron particles with a specific active lithium content as the core, and sets a three-dimensional porous carbon framework space layer on it, thus constructing a three-dimensional distributed dual-framework structure in the negative electrode phase. It is more stable than a single lithium boron alloy framework or a three-dimensional porous carbon framework space layer, which can effectively solve the problems of volume expansion of lithium metal and pulverization during cycling, and improve the cycle performance and safety of the lithium metal battery.

[0049] 2. The metal lithium battery provided by the present invention has adjustable thickness and specific capacity, abundant lithium-ion transport channels and electronic conductivity network, and simultaneously regulates the transport of lithium ions and the distribution of current, so that the composite negative electrode can perform well in terms of rate performance while maintaining good cycle life under high current.

[0050] 3. The lithium metal battery provided by the present invention further improves the cycle performance and rate performance of the composite negative electrode by adjusting the mass ratio of the three-dimensional porous carbon framework space layer to lithium boron particles, adjusting the configuration and material type of the three-dimensional porous carbon framework space layer, etc.

[0051] 4. The double-framework lithium-carbon composite material in the lithium metal battery provided by the present invention has a melting point above 200°C. This means that both the structural framework and the three-dimensional porous carbon framework space layer are resistant to high temperatures and can accommodate active lithium, which makes the lithium metal battery have excellent high temperature resistance and cycle performance, and can meet the requirements of the 200°C hot box test of power batteries.

[0052] 5. The lithium metal battery proposed in this invention has the following advantages: high specific energy, long service life, high discharge power, good high temperature performance, and is suitable for large-scale industrial applications. Attached Figure Description

[0053] To more clearly illustrate the embodiments of the present invention, the accompanying drawings used in the present invention will be briefly described below.

[0054] Figure 1 The cycling test curves of the lithium metal batteries in Examples 2, 4, 7, 9 and Comparative Example 1 are shown.

[0055] Figure 2 The graph shows the change in battery volume before and after cycling in Example 2 and Comparative Example 1. Detailed Implementation

[0056] To make the objectives, technical solutions, and advantages of this invention clearer, the invention will be further described in detail below with reference to the accompanying drawings and examples. It should be understood that the specific embodiments described herein are merely illustrative of the invention and do not limit the scope of protection of the invention. Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which this invention pertains. The technical terms used herein are for the purpose of describing specific embodiments only and are not intended to limit the invention. Those skilled in the art will recognize that, in addition to improvements to the materials, any other methods related to achieving the objectives of the invention can be used instead of the steps described, as long as the same result is obtained, the intended effect will be achieved; these will not be elaborated upon here.

[0057] Example 1

[0058] This embodiment provides a lithium metal battery, which includes a lithium-rich manganese-based positive electrode, an Al2O3-coated polypropylene separator, and a negative electrode. The negative electrode includes a lithium metal composite material layer with a thickness of 100 μm. The lithium metal composite material layer contains a granular dual-framework lithium-carbon composite material. The granular dual-framework lithium-carbon composite material has lithium boron particles with an active lithium content of 90% as the core. A three-dimensional porous carbon framework space layer formed by double-walled carbon nanotubes (outer diameter of 4 nm and length of 50 μm) is disposed on the surface of the core.

[0059] The method for preparing the lithium metal battery includes the following steps:

[0060] (1) Under argon atmosphere, 10g of lithium boron particles and 0.05g of double-walled carbon nanotubes (purchased from Xianfeng Nano Co., Ltd.) were mixed at high speed in p-xylene. The mixture was stirred at 6000rpm for 30min, then filtered and dried at 110℃ for 12h to completely remove p-xylene and obtain a double-framework lithium carbon composite material.

[0061] (2) The dual-framework lithium-carbon composite material in step (1) is formed under 30kg pressure to obtain a lithium metal composite material layer; then it is assembled with a lithium-rich manganese-based cathode and an Al2O3-coated polypropylene separator to form a lithium metal battery.

[0062] Example 2

[0063] This embodiment provides a lithium metal battery, which includes a lithium nickel cobalt manganese oxide (Ni90) positive electrode, a polyethylene separator coated with MOFs, and a negative electrode. The negative electrode includes a lithium metal composite material layer with a thickness of 50 μm. The lithium metal composite material layer contains a granular dual-framework lithium-carbon composite material. The granular dual-framework lithium-carbon composite material has lithium boron particles with an active lithium content of 50% as the core. A three-dimensional porous carbon framework space layer formed by single-walled carbon nanotubes (outer diameter of 2 nm and length of 50 μm) is disposed on the surface of the core.

[0064] The method for preparing the lithium metal battery includes the following steps:

[0065] (1) Under argon atmosphere, 5g of lithium boron particles and 5g of single-walled carbon nanotubes (purchased from Xianfeng Nano Co., Ltd.) were mixed at high speed in heptane and stirred at 10000rpm for 80min. Then, spray drying was carried out with an inlet air temperature of 230℃, an outlet air temperature of 100℃, and an atomization pressure of 0.5MPa to obtain a double-framework lithium carbon composite material.

[0066] (2) The dual-framework lithium-carbon composite material is molded under 20kg pressure to obtain a lithium metal composite material layer; then it is assembled with a lithium nickel cobalt manganese oxide Ni90 cathode and a polyethylene separator coated with MOFs to form a lithium metal battery.

[0067] Example 3

[0068] This embodiment provides a lithium metal battery, which includes a sulfurized polyacrylonitrile positive electrode, a boehm-coated polyethylene separator, and a negative electrode. The negative electrode includes a lithium metal composite material layer with a thickness of 10 μm. The lithium metal composite material layer contains a granular dual-framework lithium-carbon composite material. The granular dual-framework lithium-carbon composite material has lithium boron particles with an active lithium content of 80% as the core, and a three-dimensional porous carbon framework space layer formed by graphene (5 μm in diameter, 1-2 layers) is disposed on the surface of the core.

[0069] The method for preparing the lithium metal battery includes the following steps:

[0070] (1) Under argon atmosphere, 10g of lithium boron particles and 0.1g of graphene (purchased from Xianfeng Nano Co., Ltd.) were mixed at high speed in solvent oil D40 and stirred for 90min at a speed of 12000rpm. Then, spray drying was carried out with an inlet air temperature of 220℃, an outlet air temperature of 90℃, and an atomization pressure of 0.3MPa to obtain a double-framework lithium carbon composite material.

[0071] (2) The dual-framework lithium-carbon composite material is molded under 30kg pressure to obtain a lithium metal composite material layer; then it is assembled with a sulfurized polyacrylonitrile cathode and a boehm-coated polyethylene separator to form a lithium metal battery.

[0072] Example 4

[0073] Compared with Example 2, the only difference is that the mass of lithium boron particles in step (2) is replaced with 25g, the mass ratio of single-walled carbon nanotubes to lithium boron particles is 1:5, and all other conditions remain unchanged.

[0074] Example 5

[0075] Compared with Example 2, the only difference is that the mass of lithium boron particles in step (2) is replaced with 750g, the mass ratio of single-walled carbon nanotubes to lithium boron particles is 1:150, and all other conditions remain unchanged.

[0076] Example 6

[0077] Compared with Example 2, the only difference is that in step (2), the single-walled carbon nanotubes are replaced with a mixture of single-walled carbon nanotubes and Ketjen black in a mass ratio of 2:1.

[0078] Example 7

[0079] Compared with Example 2, the only difference is that in step (2), the single-walled carbon nanotubes are replaced with a mixture of single-walled carbon nanotubes and graphene in a mass ratio of 1:1.

[0080] Example 8

[0081] Compared with Example 2, the only difference is that the proportion of active lithium in the lithium boron particles in step (1) is replaced with 60%.

[0082] Example 9

[0083] Compared with Example 2, the only difference is that the proportion of active lithium in the lithium boron particles in step (1) is replaced with 80%.

[0084] Comparative Example 1

[0085] Compared with Example 2, the only difference is that this comparative example provides lithium boron particles, which do not include the three-dimensional porous carbon framework layer formed by single-walled carbon nanotubes, that is, step (1) is not performed in the preparation method.

[0086] Comparative Example 2

[0087] Compared with Example 2, the only difference is that in step (1), the proportion of active lithium in the lithium boron particles is replaced with 40%, while the other conditions remain unchanged.

[0088] Comparative Example 3

[0089] Compared with Example 2, the only difference is that in step (1), the proportion of active lithium in the lithium boron particles is replaced with 95%, while the other conditions remain unchanged.

[0090] Comparative Example 4

[0091] Compared with Example 2, the only difference is that in step (1), the lithium boron particles are replaced with metallic lithium particles.

[0092] Comparative Example 5

[0093] Compared with Example 2, the only difference is that lithium boron particles are replaced with lithium silicon particles, which include a lithium silicon alloy and 90% active lithium, and the lithium silicon alloy is not a three-dimensional porous structure.

[0094] Lithium metal battery performance testing:

[0095] Ten lithium metal batteries from Examples 1-9 and Comparative Examples 1-5 were prepared respectively. Matching electrolytes were injected into them for formation. Then, the cycle performance was tested at 0.5C / 1C. The test was stopped when the battery capacity decayed to 80% of the initial capacity or a short circuit occurred. The cycled batteries were subjected to nail penetration tests, and the number of batteries that caught fire or exploded was counted. The test results are shown in Table 1.

[0096] In addition, the thickness of the lithium metal batteries before and after cycling in Examples 2, 9, and Comparative Example 1 was tested. The tests in Examples 2 and 1 were as follows: Figure 2 As shown. The volume expansion rate is calculated based on the change in the thickness of the lithium metal battery before and after cycling:

[0097] Volume expansion rate = (thickness of lithium metal battery after cycling - thickness of lithium metal battery before cycling) / thickness of lithium metal battery before cycling * 100%;

[0098] Therefore, the volume expansion rate of the lithium metal battery in Example 2 is calculated to be (2.52-2.37) / 2.37*100%=6.33%;

[0099] The volume expansion rate of the lithium metal battery in Example 9 is (2.56-2.36) / 2.36*100%=8.47%;

[0100] The volume expansion rate of the lithium metal battery in Comparative Example 1 is (2.70-2.32) / 2.32*100%=16.38%.

[0101] Table 1

[0102]

[0103] The following points can be observed from Table 1:

[0104] (1) Comparing Examples 2, 4, and 5, it can be seen that the cycle performance of the lithium metal battery in Example 2 is worse than that in Examples 4 and 5. This is because the content of single-walled carbon nanotubes in Example 2 is higher than that in Examples 4 and 5, making it easier for lithium ions to gain electrons on their surface and generate lithium dendrites. In contrast, the mass of single-walled carbon nanotubes and lithium boron particles in Examples 4 and 5 is more suitable, constructing a more stable three-dimensional distributed double-framework structure in the negative electrode, effectively solving the problems of volume expansion of lithium metal and pulverization during cycling, and improving the cycle performance of the lithium metal battery. Figure 1 The test curves in the data also confirm this and its safety.

[0105] (2) Comparing Examples 2, 6, and 7, it can be seen that the cycle performance of the lithium metal battery in Example 2 is worse than that in Examples 6 and 7. This is because the three-dimensional porous framework space layer in Example 2 is of a single type, and the stability of the formed space layer is worse than that in Examples 6 and 7. Figure 1 The test curves in the data also confirm this;

[0106] (3) Comparing Examples 2, 8 and 9, it can be seen that the cycle performance of the lithium metal battery in Example 2 is worse than that in Examples 8 and 9. This is because the active lithium ratio is low in Example 2, and the lithium source consumed by replenishing the SEI film rupture and regenerating is limited. In addition, the mass of the three-dimensional porous carbon skeleton space layer and the boron in the lithium boron particles in Examples 8 and 9 is more suitable, and the structure of the negative electrode is stable.

[0107] (4) Comparing Example 2 with Comparative Examples 1-5, it can be seen that the cycle performance of the lithium metal battery in Example 2 is better than that in Comparative Examples 1-5. This may be because the negative electrode in Comparative Example 1 only has a lithium-boron alloy skeleton and lacks an outer three-dimensional porous carbon skeleton layer. Therefore, its effect on mitigating the volume expansion of active lithium and reducing current density is limited, resulting in faster capacity decay. Figure 1 As shown in the figures; in Comparative Example 2, the lithium boron particles have a low proportion of active lithium, high material hardness, poor processing performance, and limited ability to replenish lithium source consumption during cycling; in Comparative Example 3, the lithium boron particles have a high proportion of active lithium, resulting in significant volume expansion and dendrite formation, leading to poor cycle performance; in Comparative Example 4, the negative electrode only has an outer three-dimensional porous framework layer without an internal framework. Although it can alleviate the volume expansion problem of metallic lithium and inhibit the generation and growth of lithium dendrites to some extent, the effect is far less than that of Example 2; in Comparative Example 5, the core of the metallic lithium composite material of the negative electrode is lithium silicon particles, but its structure is different from that of the lithium boron particles of the present invention, and its effect on improving the cycle performance of metallic lithium batteries is limited;

[0108] (5) The safety of the lithium metal battery in this invention is significantly higher than that of the lithium metal batteries in Comparative Examples 1-5. This is because the lithium metal battery in this invention adopts a unique negative electrode structure, which significantly improves the safety of the lithium metal battery.

[0109] The above are merely preferred embodiments of the present invention and not examples. All modifications, equivalent substitutions, and improvements made within the spirit and principles of the present invention should be covered within the scope of the claims of the present invention.

Claims

1. A lithium metal battery, characterized in that, The lithium metal battery includes a positive electrode, a separator, and a negative electrode. The negative electrode contains a lithium metal composite material layer, which contains particulate dual-framework lithium-carbon composite material. The granular dual-framework lithium-carbon composite material has lithium boron particles as its core. The core contains a lithium boron alloy structural framework and active lithium. A three-dimensional porous carbon framework space layer formed by nano-carbon materials is provided on the surface of the core. The active lithium in the lithium boron particles accounts for 50%-90% of the total mass.

2. The lithium metal battery according to claim 1, characterized in that: The thickness of the negative electrode is 1-100 μm, preferably 5-50 μm; Preferably, the volume expansion rate of the lithium metal battery before and after cycling is ≤15%.

3. The lithium metal battery according to claim 1 or 2, characterized in that: The average particle size of the dual-framework lithium-carbon composite material is 1-200 μm, preferably 5-100 μm; Preferably, the melting point of the dual-framework lithium-carbon composite material is >200℃; Preferably, the shape of the lithium boron particles includes at least one of spherical, ellipsoidal, near-spherical, rod-shaped, or irregular shapes; Preferably, the active lithium content in the lithium boron particles is 50%-80% by mass.

4. The lithium metal battery according to any one of claims 1-3, characterized in that: The structure of the three-dimensional porous carbon framework spatial layer is a three-dimensional porous network structure formed by the interweaving of at least one of linear, tubular or sheet-like nano-carbon materials; Preferably, the nano-carbon material includes at least one of carbon nanofibers, single-walled carbon nanotubes, few-walled carbon nanotubes, multi-walled carbon nanotubes, or graphene. Preferably, the composite material further includes granular nano-carbon material, preferably at least one of biochar, conductive graphite, acetylene black, Ketjen black, Super P or Cabot carbon black, wherein the granular carbon material is distributed at any position on the surface of lithium boron particles, on the surface of the three-dimensional porous carbon skeleton space layer or in the pores.

5. The lithium metal battery according to any one of claims 1-4, characterized in that: The mass ratio of the three-dimensional porous carbon framework space layer to lithium boron particles is 1:(1-200), preferably 1:(5-150).

6. The lithium metal battery according to any one of claims 1-5, characterized in that: The mass ratio of the three-dimensional porous carbon framework space layer to the boron in the lithium boron particles is 1:(0.1-100), preferably 1:(1-50).

7. The lithium metal battery according to any one of claims 1-6, characterized in that, The diaphragm includes polypropylene, polyethylene, polypropylene / polyethylene composite diaphragm or polypropylene, polyethylene, or polypropylene / polyethylene composite diaphragm with coating; Preferably, the coating comprises at least one of boehmite, alumina, MOFs, COFs, solid electrolyte, sulfonated membrane, polyvinylidene fluoride, aramid, or polyimide; Preferably, the negative electrode further includes a current collector, which includes at least one of pure copper foil, carbon-coated copper foil, roughened copper foil, nickel foil, copper-nickel alloy foil, copper-tin composite foil, stainless steel foil, carbon cloth, or carbon paper. Preferably, the positive electrode comprises at least one of lithium iron phosphate, lithium manganese iron phosphate, lithium nickel cobalt manganese oxide, lithium nickel cobalt aluminum oxide, lithium manganese oxide, lithium cobalt oxide, lithium nickel oxide, elemental sulfur, lithium-rich manganese-based oxide, polyacrylonitrile sulfide, or vanadium pentoxide, and more preferably at least one of lithium nickel cobalt manganese oxide, lithium nickel cobalt aluminum oxide, or lithium-rich manganese-based oxide.

8. A method for preparing a lithium metal battery according to any one of claims 1-7, characterized in that, The method includes: (1) Under an inert gas protective atmosphere, an organic solvent, lithium boron particles and carbon materials are mixed, wherein the carbon materials include nano-carbon materials and optionally, particulate nano-carbon materials, and then dispersed at high speed and / or spray-dried at a speed of more than 6000 rpm, thereby setting a three-dimensional porous framework space layer formed by the nano-carbon materials on the surface of the lithium boron particles to obtain a dual-framework lithium-carbon composite material; wherein the organic solvent is inert to the lithium boron particles; (2) The dual-framework lithium-carbon composite material from step (1) is prepared into a negative electrode using a dry process; (3) Assemble the positive electrode, separator and negative electrode into the metal lithium battery.

9. The preparation method according to claim 8, characterized in that, The organic solvent in step (1) includes any one or a combination of at least two of the following: liquid alkanes with 4-20 carbon atoms, liquid cycloalkanes with 4-20 carbon atoms, toluene, xylene, solvent oil, liquid paraffin, tetrahydrofuran, N-methylpyrrolidone, N,N-dimethylformamide, or silicone oil. Preferably, the mass ratio of the organic solvent to the lithium boron particles in step (1) is (10-100):1, more preferably (20-50):

1.

10. The method according to claim 8 or 9, characterized in that, The dry process in step (2) includes at least one of roll pressing and / or flat pressing, electrostatic spraying, or adhesive fiberization. Preferably, the adhesive comprises at least one of polytetrafluoroethylene, polyvinylidene fluoride, or styrene-butadiene rubber; Preferably, the mass ratio of the binder to the dual-framework lithium-carbon composite material is (1-20):(80-99), and more preferably (3-10):(90-97).

Citation Information

Patent Citations

  • Graphitized carbon material and preparation method thereof, metal lithium negative electrode for secondary battery and battery

    CN117446798A